Emotional storytelling in building global brand loyalty: a cb-sem model approach - Baihaqi Alfakihuddin, Muhammad Lukman (Institute of Computer Science (IOCS), 2025)
In the digital era, emotional storytelling has emerged as a strategic tool for global brands to foster deeper consumer relationships and long-term loyalty. This study investigates the effects of Emotional Brand Attachment (EBA), Brand Love (BL), Electronic Word-of-Mouth (eWOM), and Psychological Brand Ownership (PBO) on Brand Identity (BI) and Consumer Loyalty (CL). Using Covariance-Based Structural Equation Modeling (CB-SEM), data from 395 Indonesian respondents were analyzed. Results indicate that EBA and PBO significantly influence both BI and CL, while BL and eWOM primarily drive CL. BI is also shown to mediate these relationships, reinforcing its role in sustaining consumer loyalty. The model demonstrates strong fit (RMSEA = 0.035, CFI = 0.970, TLI = 0.981) and explanatory power (R² = 96.5% for BI; R² = 98.1% for CL). These findings highlight the critical role of emotionally rich, digital brand narratives in shaping consumer-brand relationships, offering practical insights for marketers to design emotionally resonant strategies that build identity, ownership, and loyalty in competitive global markets